Mesocarnivores affect hispid cotton rat (Sigmodon hispidus) body mass - Morris, Gail (Sci Rep, 2019)
Predator communities are changing worldwide: large carnivores are declining while mesocarnivores (medium-sized mammalian predators) are increasing in number and ecological influence. Predator choice of prey is not random and different predators select prey with different characteristics. Changes in predator communities can change predation patterns experienced by prey. Little is known about how mesocarnivore communities influence prey morphology. We used 14 years of mark-recapture data to investigate how mesocarnivore exclusion affected body mass of hispid cotton rats (Sigmodon hispidus). Finding adult male cotton rats were 9% heavier with mesocarnivore exclusion, we developed hypotheses to explain this observation. Greater adult male body mass in exclosures resulted from: (1) a non-significant trend of increased survival of large males, (2) faster juvenile male growth during the fall and a similar non-significant trend among adult males, and (3) spatial partitioning by size among males. Taxa-specific predation rates (i.e., rates of predation by snakes, raptors, or mesocarnivores) did not differ among male body mass classes. Mesocarnivores disproportionately preyed on large females while raptors targeted small females, but female body mass was not influenced by mesocarnivore exclusion. Changes in predator communities can result in multiple small effects that collectively result in large differences in prey morphology.